Effects of Solid-State Stretching on Microstructure Evolution and Physical Properties of Isotactic Polypropylene Sheets - Huajian Ji (Polymers, 2019)
The microstructure evolution of an isotactic polypropylene (iPP) sheet during solid-state stretching was studied. The transition of the spherulites—cylindrites was evaluated using in-situ two-dimensional wide-angle and small-angle X-ray scattering methods. The crystallinity of stretched iPP sheets was characterized by differential scanning calorimetry. The crystal morphology was observed by means of scanning electron microscopy. It was found that the differences of crystal microstructure of the iPP sheet depended on the stretching strain, which promoted the orientation of molecular chains. Amorphous molecular chains in the spherulites oriented and formed into a mesophase near the yield point, and the partially ordered mesophase was further stretched to form an oriented cylindrite structure after the yield point. The highest relative content of cylindrites appeared at 15% strain. Notably, as the amorphous phase embedded into the lamellae layer, the crystal size decreased with the increase of strain, which indicated that the crystallinity of the stretched iPP sheet was much higher than that of unstretched iPP sheet. The induced cylindrites structure played a more important role in improving the mechanical properties and heat resistance of iPP sheets. Compared with the unstretched iPP sheets, the tensile strength increased by 28%, the notch impact toughness significantly increased by 78%, and the vicat softening point increased from 104 to 112 °C.